2015
DOI: 10.1515/ijfe-2014-0099
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chemical, Biochemical and Microbiological Quality in Tomato Using Multivariate Analysis

Abstract: Tomato quality is determined by metabolite content which is governed by post-harvest physiological changes. A 30-day full factorial experiment investigated pre-packaging, disinfection and storage temperatures on 18 different biochemical, microbiological, enzymatic and subjective quality attributes of tomato quality. Principal component analysis revealed associations among the variables such as PC1 (28.85%): coliform/enzymatic softening; PC2 (21.52%): free sugars/sweetness; and PC3 (18.20%): sucrose hydrolysis/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Alimi, Shittu and Sanni (2014) reported that the final quality is dependent on the interaction effects of the different treatments. Building multiple factors, statistical analysis to study the effects of continuous and categorical variables and covariates is vital for the determination of tomato quality (Binder, Sauerbrei, & Royston, 2013;Sobratee & Workneh, 2015). A multivariable regression model development is dependent on the selection of covariates that related to the response of interests and searching for an appropriate efficient model for continuous covariates (Binder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alimi, Shittu and Sanni (2014) reported that the final quality is dependent on the interaction effects of the different treatments. Building multiple factors, statistical analysis to study the effects of continuous and categorical variables and covariates is vital for the determination of tomato quality (Binder, Sauerbrei, & Royston, 2013;Sobratee & Workneh, 2015). A multivariable regression model development is dependent on the selection of covariates that related to the response of interests and searching for an appropriate efficient model for continuous covariates (Binder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This approach can be used to reduce the number of continuous variables to put in the representative group by identifying patterns in a data set and help to eliminate the repetition in a univariate analysis (Iezzoni & Pritts, 1991;Martens & Martens, 2001). The PC is the linear combination of variables that has maximum variance subject to normalization constraints on the coefficients (eigenvectors) (Harrell, 2015) and the total variance created by each PC evaluated as eigenvalue (Iezzoni & Pritts, 1991;Martens & Martens, 2001;Sobratee & Workneh, 2015).…”
Section: Introductionmentioning
confidence: 99%